UCAPAN SYUKUR DALAM ACARA ADAT SYUKURAN PANEN DI NEW YORK CITY DAN TANA TORAJA (SUATU ANALISIS KONTRASTIF) - WOWILING, RICHARD ANDREW OCTIBELS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT Â  This research entitled â€œUcapan Syukur dalam Acara Adat Syukuran Panen di New York City dan Tana Torajaâ€ is an attempt to analyze the kinds of ceremonies held in harvest thanksgiving. In obtaining the traditional ceremonies, the data were collected by interviewing some native speaker and searched in internet. Descriptive method is applied to describe and analyze the collected data by employing Hymesâ€™ concept in the ethnography of communication i.e. the acronym SPEAKING (S=Setting and Scene, P=Participants, E=Ends, A=Act Sequence, K=Keys, I=Instrumentalities, N=Norms of Interaction and Interpretation, G=Genre) The result of this research shows that some traditional ceremonies held in Harvest Thanksgiving in New York City and Tana Toraja. They are Macyâ€™s Thanksgiving Parade in New York City as the opening ceremony of Thanksgiving day by using modern touched, such as marching band, cheerleaders, some famous band, giant balloons, floats, clowns, broadway shows, Thanksgiving dinner that was held in New York City in the night when all family member get together for a special meal and ecclesiastical ceremony that held before afternoon in Tana Toraja when Harvest Thanksgiving and some traditional dances shown after the ecclesiastical ceremony. The differences are ecclesiastical ceremony was not exist in New York Harvest Thanksgiving and Parades were not find in Tana Toraja. Key words: Traditional Ceremony, Harvest Thanksgiving, Contrastive Analysis Â